LEGISLATION AS SOCIAL INTERVENTION - AGUIAR DE DEUS, PAULO RICARDO (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2022)
The idea that legislation causes intervention is an issue that usually calls for an analysis of its economic impacts exclusively in the market system. The aim of this paper is to determine whether legislation can be understood as intervention per se, and, if so, to what extent theories of intervention can be applied to it. Through exploratory methodology and literature review, it was possible to conclude not only that the intervention theory is perfectly applicable to legislation as a social intervention, but also that without the use of these theories it is not possible to understand the dimension of the social impact caused by legislation on society. In a civilization of private law, social relations unfold spontaneously and organically, while in societies of public law, human relations need to be artificially protected and human action is largely conducted by central planning bodies, as it happens in a planned economy. It is this scenario that favors the creation of pressure groups in legislative houses, enforcing malinvestments as they represent distortions in social relations through coercion, just as intervention does in the economy. In the same way that economic intervention practically requires an indeterminate chain of other interventions planning the economy, legislative intervention calls for new legislation, degrading social life, corrupting the very idea of ​​freedom and mutual cooperation.